2015
DOI: 10.1093/cid/civ365
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Spatial Analysis ofMycobacterium tuberculosisTransmission in a High-Incidence Urban Setting

Abstract: Spatial and genotypic clustering of M. tuberculosis isolates revealed ongoing active transmission of tuberculosis caused by a small subset of strains in specific neighborhoods of the city. Such information provides an opportunity to target tuberculosis transmission control, such as through rigorous and more focused contact investigation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Several studies showed that TB is associated with conditions that express vulnerability to social determinants, such as, HIV co-infection, drug abuse, immigration, unemployment, low educational level, poor housing quality and crowded living conditions 3,4,6 . Wong et al 32 analyzing the distribution of TB case notifications in Thailand (2010) according to the population density, observed an overlap of high population density areas in areas with greater amount of TB case notifications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that TB is associated with conditions that express vulnerability to social determinants, such as, HIV co-infection, drug abuse, immigration, unemployment, low educational level, poor housing quality and crowded living conditions 3,4,6 . Wong et al 32 analyzing the distribution of TB case notifications in Thailand (2010) according to the population density, observed an overlap of high population density areas in areas with greater amount of TB case notifications.…”
Section: Discussionmentioning
confidence: 99%
“…Their use in public health provides a better understanding of the dynamics of the disease processes and diffusion as well as the relationship between the disease and the environment 1 . Some studies have evaluated tuberculosis (TB) distribution using spatial analysis tool [2][3][4][5][6][7] . In Portugal, the spatial distribution of TB incidence rates (2004)(2005)(2006) showed high values in large cities (Porto, Lisbon and Setúbal Peninsula), in north-eastern and in southern Portugal 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the characteristics of pulmonary tuberculosis (PTB)exist an obvious spatial-temporal heterogeneity at the national level or the provincial level (Tweya et al, 2013;Ribeiro et al, 2015;Kolifarhood et al, 2015;Hassarangsee et al, 2015), and it is believed that a better understanding of the patterns on spatial-temporal heterogeneity of smear positive PTB are important to formulate effective national prevention and control strategies, and allocate the limited health resources of national TB program (NTP) (Areias et al, 2015;Wubuli et al, 2015). As the most infectious form of TB and the main source of infection, prolonged exposure to smear positive PTB patient are highly susceptible to infect with TB, meanwhile, the longer, the more dangerous (Chen et al, 2016;Shi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36] Strategic measures of prevention are urgent to the incidence control and decreasing in significantly affected regions, reinforce the need for technologies such as geocodification and genotyping as important tools in TB control and prevention in priority areas, the utilization of spatial analysis to identify local particularities, geographic, cultural and socioeconomic differences, valuing the specific needs of educative actions about the disease. [37][38][39][40][41][42][43][44]…”
Section: Strategic Measures To Fight Tuberculosismentioning
confidence: 99%